Risk of Psychiatric Disorders Following Symptomatic Menopausal Transition: A Nationwide Population-Based Retrospective Cohort Study. Issue 6 (February 2016) - Hu, Li-Yu; Shen, Cheng-Che; Hung, Jeng-Hsiu; Chen, Pan-Ming; Wen, Chun-Hsien; Chiang, Yung-Yen; Lu, Ti
Abstract : Abstract: Menopausal transition is highly symptomatic in at least 20% of women. A higher prevalence of psychiatric symptoms, including depression, anxiety, and sleep disturbance, has been shown in women with symptomatic menopausal transition. However, a clear correlation between symptomatic menopausal transition and psychiatric disorders has not been established. We explored the association between symptomatic menopausal transition and subsequent newly diagnosed psychiatric disorders, including schizophrenia as well as bipolar, depressive, anxiety, and sleep disorders. We investigated women who were diagnosed with symptomatic menopausal transition by an obstetrician-gynecologist according to the data in the Taiwan National Health Insurance Research Database. A comparison cohort comprised age-matched women without symptomatic menopausal transition. The incidence rate and the hazard ratios of subsequent newly diagnosed psychiatric disorders were evaluated in both cohorts, based on the diagnoses of psychiatrists. The symptomatic menopausal transition and control cohorts each consisted of 19, 028 women. The incidences of bipolar disorders (hazard ratio [HR] = 1.69, 95% confidence interval [CI] = 1.01–2.80), depressive disorders (HR = 2.17, 95% CI = 1.93–2.45), anxiety disorders (HR = 2.11, 95% CI = 1.84–2.41), and sleep disorders (HR = 2.01, 95% CI = 1.73–2.34) were higher among the symptomatic menopausal transition women than in the comparison cohort. After stratifying for follow-up duration, the incidence of newly diagnosed bipolar disorders, depressive disorders, anxiety disorders, and sleep disorders following a diagnosis of symptomatic menopausal transition remained significantly increased in the longer follow-up groups (1–5 and ≥ 5 years). Symptomatic menopausal transition might increase the risk of subsequent newly onset bipolar disorders, depressive disorders, anxiety disorders, and sleep disorders. A prospective study is necessary to confirm these findings.